2020
DOI: 10.3390/ijms21030724
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomic Analysis of Zebrafish Glucagon Receptor Mutant Reveals Its Regulated Metabolic Network

Abstract: The glucagon receptor (GCGR) is a G-protein-coupled receptor (GPCR) that mediates the activity of glucagon. Disruption of GCGR results in many metabolic alterations, including increased glucose tolerance, decreased adiposity, hypoglycemia, and pancreatic α-cell hyperplasia. To better understand the global transcriptomic changes resulting from GCGR deficiency, we performed whole-organism RNA sequencing analysis in wild type and gcgr-deficient zebrafish. We found that the expression of 1645 genes changes more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…In order to study the changes in GCGR-deficient animal, as well as for screening chemical modifiers to mitigate these side effects, we generated a GCGR knockout zebrafish model (Li et al, 2015 ). Our studies suggested that gcgr −/− mutant zebrafish displayed phenotypes similar to Gcgr -deficient mice, which had lower free glucose content, higher glucagon content, α-cell hyperplasia, and accentuation of fat in the liver (Li et al, 2015 ; Kang et al, 2020 ). We further analyzed the regulated metabolic network in transcriptional level by RNA-seq and found that many genes related to metabolism of carbohydrates, lipids, and amino acids were dysregulated in gcgr −/− mutant zebrafish (Kang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In order to study the changes in GCGR-deficient animal, as well as for screening chemical modifiers to mitigate these side effects, we generated a GCGR knockout zebrafish model (Li et al, 2015 ). Our studies suggested that gcgr −/− mutant zebrafish displayed phenotypes similar to Gcgr -deficient mice, which had lower free glucose content, higher glucagon content, α-cell hyperplasia, and accentuation of fat in the liver (Li et al, 2015 ; Kang et al, 2020 ). We further analyzed the regulated metabolic network in transcriptional level by RNA-seq and found that many genes related to metabolism of carbohydrates, lipids, and amino acids were dysregulated in gcgr −/− mutant zebrafish (Kang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 91%
“…Among all of these changed lipids in glycerophospholipid metabolism, LPC (16:0) (−2.10) and LPC (P-18:0) (−1.91) were altered the most ( Supplementary Table 1 ). To further investigate how GCGR affects lipid metabolism in multiple levels, we also carried out the integrated analysis of metabolomics data with our previous transcriptomics data (Kang et al, 2020 ). We found 29 significantly altered transcripts ( Supplementary Table 3 ) were associated with glycerophospholipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations